A Pilot Study Examining the Effectiveness of the PEERS Program on Social Skills and Anxiety in Adolescents with Autism Spectrum Disorder - Hill, Trenesha L. (J Dev Phys Disabil, 2017)
The Program for the Evaluation of the Enrichment of Relational Skills (PEERS), a social skills intervention for high functioning adolescents with autism spectrum disorder (ASD), has been proven efficacious in randomized control trials. However, the effectiveness of the PEERS program in community settings has not been studied. The present small-scale pilot study examined the effectiveness of the PEERS program in a community setting. Five adolescents and their caregivers participated in the PEERS intervention. Results indicated that the adolescents showed significant improvement in their social engagement, social cognition, social communication, social motivation, and knowledge of PEERS skills and concepts from pre- to post-intervention. Furthermore, adolescents showed significant reductions in their internalizing and autistic symptoms from pre- to post-intervention. The findings from this small-scale pilot study support the effectiveness of the PEERS program in community-based settings.